Structuring place-making in a multicultural city - Britz, Banie (Acta Structilia, 2017)
Urban designers in South Africa, as in the rest of the world, are faced with cities inhabited by people from many diverse cultures. If it is accepted that to dwell meaningfully, the inhabitants of the city should identify with their habitat and be able to understand how to appropriate it, then the structuring of the city should be an expression of many diverse cultural symbol-systems. The multicultural nature of the modern city makes it impossible to choose a particular place-making strategy. Because of their training, most urban designers tend to avoid the multicultural issue and opt for a westernised functional/technical approach. This paper first samples some of the vast variety of experiences that constitute a sense of place, not only in various cultures, but also in different periods in history. It then highlights a useful model that could serve as a paradigm for the unified multicultural city. This configuration would allow for the simultaneous expression of the symbol-systems of many cultures, yet link it with present globalising trends.